2009
DOI: 10.1371/journal.pone.0006126
|View full text |Cite
|
Sign up to set email alerts
|

Replication Independent Formation of Extrachromosomal Circular DNA in Mammalian Cell-Free System

Abstract: Extrachromosomal circular DNA (eccDNA) is a pool of circular double stranded DNA molecules found in all eukaryotic cells and composed of repeated chromosomal sequences. It was proposed to be involved in genomic instability, aging and alternative telomere lengthening. Our study presents novel mammalian cell-free system for eccDNA generation. Using purified protein extract we show that eccDNA formation does not involve de-novo DNA synthesis suggesting that eccDNA is generated through excision of chromosomal sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…So far, knowledge on mechanisms of eccDNA generation is limited. Proposed repair mechanisms include both the replication-based mechanisms and non-replicative mechanisms 36 40 . The non-replicative repair mechanisms mainly include NAHR, NHEJ and MMEJ.…”
Section: Discussionmentioning
confidence: 99%
“…So far, knowledge on mechanisms of eccDNA generation is limited. Proposed repair mechanisms include both the replication-based mechanisms and non-replicative mechanisms 36 40 . The non-replicative repair mechanisms mainly include NAHR, NHEJ and MMEJ.…”
Section: Discussionmentioning
confidence: 99%
“…As aforementioned, it is suggested that genomic instability, apart from DNA replication and replication-related repair attempts, are primarily involved. Accordingly, augmented eccDNA load is found as a result of double-strand break (DSB) induction [36], which thus might operate as a trigger for eccDNA formation both in a physiological and pathological context.…”
Section: Eccdna Abundance-a Results Of Genomic Instability and Dna Repairmentioning
confidence: 99%
“…Of note, several lines of evidence indicate that eccDNA biogenesis does not absolutely depend on homologous recombination (HR) but can be produced by excision from chromosomal sequences, e.g., during the process of HR-independent DNA repair [36]. It has even been suggested that neither HR nor non-homologous end joining (NHEJ; or classical NHEJ, c-NHEJ) are required for eccDNA production and that the eccDNA amount is weakly correlated with the proliferation rate of an individual tissue type [9].…”
Section: Eccdna Abundance-a Results Of Genomic Instability and Dna Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…CAGFs belong to extrachromosomal ssDNA molecules and their copy numbers are increased after CQ treatment [11], which distinguishes them from double-stranded extrachromosomal circular DNA (eccDNA) molecules found in all eukaryotes [39] [40]. Although eccDNA molecules can be generated by sublethal drug exposure [41] and levels of total eccDNA molecules have been elevated after exposure of organism to genotoxic agent [42], the copy number of every single eccDNA molecule can not be increased after exposure to genotoxic agent because the formation of eccDNA molecules is through excision of chromosomal sequences and no de-novo DNA synthesis is involved [43]. The eccDNA-related excision of chromosomal sequences could be considered as a kind of genoautotomy in which nonlethal double-stranded genomic-DNA fragments are excised from chromosomes [14].…”
Section: Discussionmentioning
confidence: 99%